MICROBIOMES ASSOCIATED WITH CLINICAL STAGES OF GASTRIC CANCER - KHAN, S; IQBAL, N; ASHFAQ, MT; FAROOQ, U; FARID , MI; AHMAD, W; AHMAD , M (Biological and Clinical Sciences Research Journal, 2024)
Gastric cancer, one of the most prevalent and deadly forms of cancer worldwide, is influenced by a multitude of factors, including genetic predisposition, environmental exposures, dietary habits, and infections. Objectives: The main objective of this audit is to find the microbiomes associated with the clinical stages of gastric cancer. Methods: This clinical audit was done in DHQ Teaching Hospital DI Khan from September 2023 to March 2024. This is a cross-sectional study design. The study included a total of 175 patients diagnosed with gastric cancer. Gastric tissue and fluid samples were collected during endoscopic examinations. Biopsy samples were taken from the tumor and adjacent non-tumorous tissues to assess the local microbiome. Additionally, gastric lavage fluid was collected to capture the microbial community within the stomach lumen. Results: Data were collected from 175 patients. Helicobacter pylori abundance negatively correlated with tumor size (r = -0.35, p < 0.01), suggesting a potential protective role or association with smaller tumors. In contrast, Fusobacterium nucleatum exhibited positive correlations with more aggressive disease features: a correlation coefficient of 0.42 (p < 0.01) with lymph node involvement and 0.50 (p < 0.001) with distant metastasis. Conclusion: The gastric microbiome undergoes significant diversity, composition, and function alterations across different clinical stages of gastric cancer.